Prognostic Value And Clinical Impact Of EBV And PDL1 Expression In Classical Hodgkin Lymphoma (Journal of Pharmaceutical Negative Results, 2023)
Background Classic Hodgkin Lymphoma (cHL) accounts for approximately 90% of Hodgkin lymphoma, while nodular lymphocyte-predominant HL (NLPHL) accounts for the remainder of cases. However, the distribution of histologic subtypes of CHL varies based on geography, socioeconomic factors, race/ethnicity, and age. Epstein-Barr virus (EBV) play a role in pathobiology of significant fraction of HL cases as EBV infected tumor cells express subset of EBV genes including LMP1, LMP2 Aim The aim of this study was to investigate and assess EBV and PDL 1 expression as prognostic markers in classical Hodgkin lymphoma and their relation to International Prognostic Score (IPS). Methods The current study was a prospective study that included patients aged ≥ 18 years with pathologically proven classical Hodgkin lymphoma. But we excluded patients received previous chemotherapy or radiotherapy, patients with advanced medical comorbidity and patients with other malignancy. Performance status was classified according to Eastern Cooperative Oncology Group (ECOG). Immunohistochemistry staining (PDL1 and EBV) was done for the obtained biopsies. Results PDL1 was positive in 75 patients (89.3%), while 69 (82 %) of the patients were EBV negative. Near 83% of the patients with EBV positive were presented with early-stage Hodgkin lymphoma with favorable risk, patients with neutrophils lymphocytes ratio less than 3, near 93,6 % of the patients achieved complete remission. Conclusion Hodgkin lymphoma is considered highly curable disease with low mortality. EBV and PDL1 should be investigated on larger number of cases to evaluate their predictive and prognostic value. Neutrophil lymphocyte ratio is an important predictive and prognostic marker for Hodgkin lymphoma which is inexpensive, easily accessible test from a CBC at diagnosis, simple, widely available, and can be easily used in clinical practice especially in resource-poor areas.